Petrostate climate diplomacy at COP28 - Sembiring, Margareth (2024)
The United Arab Emirates’ (UAE) COP28 presidency this year was marked by a different approach in global climate discussions. Despite the many differences and controversies encountered, petrostate climate diplomacy continues to be relevant in a world that is far from ready to let go of fossil fuels.